Isolation of Mitochondria From Fresh Mice Lung Tissue - Caldeira, Dayene de Assis Fernandes; Oliveira, Dahienne Ferreira de; Cavalcanti-de-Albuquerque, João Paulo; Nascimento, Jose Hamilton Matheus; Zin, Walter Araujo; Maciel, Leonardo (Frontiers in Physiology, 2021)
Direct analysis of isolated mitochondria enables a better understanding of lung dysfunction. Despite well-defined mitochondrial isolation protocols applicable to other tissues, such as the brain, kidney, heart and liver, a robust and reproductive protocol has not yet been advanced for the lung. We describe a protocol for mitochondria isolation from lung tissue aiming for the functional analyses of mitochondrial O2 consumption, transmembrane potential, ROS formation, ATP production, and swelling. We compared our protocol to that used for heart mitochondrial function, well established in the literature, and achieved similar results.